Analisis Peranan Guru Pendidikan Agama Kristen Sebagai Pembimbing Dalam Upaya Mengatasi Kesulitan Belajar Siswa Di Kelas VIII SMP Negeri 2 Muara Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Debora Simamora; Raikhapoor Raikhapoor; Maria Widiastu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to determine the role of knowledge played by Christian Religious Education teachers as mentors in efforts to overcome students' learning difficulties in class VIII of SMP Negeri 2 Muara for the 2023/2024 academic year. The research hypothesis is that the role of Christian Religious Education teachers as mentors in efforts to overcome the learning difficulties of class VIII students at SMP Negeri 2 Muara for the 2023/2024 academic year is > 75% of what was expected. The population is all students in class VIII of SMP Negeri 2 Muara for the 2023/2024 academic year who are Protestant Christians, totaling 102 people. The research sample was determined by random sampling at 35% from 102 people, namely 36 people. This research method is a descriptive quantitative inferential method with a research instrument using a questionnaire. Hypothesis testing using the t test formula obtained a value of tcount=10.576>ttable=2.042. The tcount value is in the curve area of ​​rejection of H0 and acceptance of Ha. Thus, it can be concluded that the accepted research hypothesis is that the role of Christian Religious Education teachers as mentors in efforts to overcome the learning difficulties of class VIII students at SMP Negeri 2 Muara Belajar in 2023/2024 is > 75% of the expected 84.84%. However, there are several teacher roles that must be improved, including: 1) The role of providing reinforcement in the form of enthusiasm, with a value of 3.22. 2) Role in helping students to make good friends with other friends, with a value of 3.08. 3) Role in providing feedback to students who are slow in learning, with a value of 3.19. 4) Role in using media or learning tools, with a value of 3.17. Some of these roles are in the good category and it is hoped that teachers will be able to achieve their achievements so that they become very good.